Лирика Пушкина - Лахостский Кирилл Павлович (Серия "В помощь учащимся старших классов", 1959)
Экземпляры: КХ (20220415) / Инвентарный номер: 0103650 / Сис.шифр: 8Р1 / Авт.знак: Л 29 / ГРНТИ: 17 / ББК: 83